Integrative Analysis of lncRNA-miRNA-mRNA Regulatory Network Reveals the Key lncRNAs Implicated Potentially in the Differentiation of Adipocyte in Goats - He, Changsheng; Wang, Yong; Zhu, Jiangjiang; Li, Yanyan; Chen, Juan; Lin, Yaqiu (Frontiers in Physiology, 2022)
Goats are popular in China because of their superior meat quality, delicate flesh, and unique flavor. Long noncoding RNAs (lncRNAs) play important roles in transcriptional and post-transcriptional regulation of gene expression. However, the effects of lncRNAs on adipocyte differentiation in goat hasn’t been fully elucidated yet. In this investigation, we performed RNA-Seq analysis of intramuscular and subcutaneous adipocytes from Jianzhou Daer goat before and after differentiation, including both intramuscular preadipocytes (IMPA) vs intramuscular adipocytes (IMA) and subcutaneous preadipocytes (SPA) vs subcutaneous adipocytes (SA). A total of 289.49 G clean reads and 12,519 lncRNAs were obtained from 20 samples. In total, 3,733 differentially expressed RNAs (182 lncRNAs and 3,551 mRNAs) were identified by pairwise comparison. There were 135 differentially expressed lncRNAs (DELs) specific to intramuscular adipocytes, 39 DELs specific to subcutaneous adipocytes, and 8 DELs common to both adipocytes in these 182 DELs. Some well-known and novel pathways associated with preadipocyte differentiation were identified: fat acid metabolism, TGF-beta signaling pathway and PI3K-Akt signaling pathway. By integrating miRNA-seq data from another study, we also identified hub miRNAs in both types of fat cells. Our analysis revealed the unique and common lncRNA-miRNA-mRNA networks of two kinds of adipocytes. Several lncRNAs that regulate potentially goat preadipocyte differentiation were identified, such as XR_001918 647.1, XR_001917728.1, XR_001297263.2 and LNC_004191. Furthermore, our findings from the present study may contribute to a better understanding of the molecular mechanisms underlying in goat meat quality and provide a theoretical basis for further goat molecular breeding.